“Partir es necesario, pues solo así puedo vivir”: Enfermedad y fantasía en Peregrinaciones de una alma triste (1876) de Juana Manuela Gorriti - Torres Astocóndor, Carlos (2019)
This article aims to analyze the opening scene of the Juana Manuela Gorriti novel’s, Peregrinaciones de una alma triste ([1876] 2006). For this, two interpretations are proposed on the figure of Laura, protagonist of the story. The first argues that tuberculosis, a disease that Laura suffers, is constituted as a symptom that discovers the impossibility of representing women through national projects erected by the élite criolla and, on the other, disrupts their insertion in the social dynamic. The second interpretation proposes that Laura’s gesture in her escape is a “going through the phantasmic screen” that cover women, constituted by nineteenth-century national rhetoric, by showing their inconsistencies. On this way, it is concluded that the novel, through travel, is in the search for an “alternative knowledge” because, on the one hand, the national project has been dismantled and, on the other, it affirms a continuous displacement through different spaces to establish new social ties with the communities that are in the margins or outside this project.